THE IMPROVEMENT OF STUDENT LEARNING OUTCOMES IN IPS LEARNING WITH ROLE PLAYING METHOD - astuti, widia; s, farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to describe the improvement of student learning outcomes in social studies learning using the Role Playing method in class V SD. This type of research is Classroom Action Research (CAR) using qualitative and quantitative approaches. Subjects in this study were students and class V teachers totaling 16 people. This research was carried out in 2 cycles consisting of planning, implementing, observing and reflecting. Research results from cyclulus I to Cycle II. (a) Cycle 1 learning planning is 80.32% increased to 92.85% in cycle 2. (b) Implementation of learning from the aspect of teacher in cycle 1 with an average of 80.20,% increased to 91.5%. in cycle 2, from the aspect of students in cycle 1 with an average of 77.62% increased to 89.58% in cycle 2. (c) Learning outcomes obtained by students in cycle 1 obtained an average grade of 78.42 increased to 85 , 02% in cycle 2. Thus, the Role Playing method can improve student learning outcomes in social studies learning in class V SD. Keywords: IPS, role playing method.